Incorporation of calcium aluminate and zirconia in polymethylmethacrylate (PMMA) bone cement for biomedical applications: study of in vitro osteogenesis - Lupp, Juliana dos Santos; Almeida-Silva, Luis Augusto de; Ramos , Nathalia de Souza; Oliveira , Ivone Regina de; Oliveira , Felipe Eduardo de; Avelino , Sarah de Oliveira Marco; Gonçalves , Isabela dos Santos; Vaconcellos , Luana Marotta Reis de (Brazilian Dental Science, 2025)
Objective: To evaluate the effects of incorporating calcium aluminate cement (CAC) and monoclinic zirconia (Z) into polymethylmethacrylate (PMMA) bone cement on in vitro osteogenesis. Material and Methods: Samples of pure PMMA, PMMA+CAC 7.5% (wt%) and PMMA+Z 7.5% (wt%) were prepared. The formulations were characterized by scanning electron microscopy, energy-dispersive spectroscopy, Fourier-transform infrared spectroscopy, and wettability analysis. For biological assessment, mesenchymal stem cells derived from Wistar rat femurs were cultured on the samples. Cellular response was analyzed by cell viability assay, protein synthesis, alkaline phosphatase (ALP) activity, tumor necrosis factor-alpha (TNF-α) expression by ELISA, and mineralized nodule formation. Results: All groups exhibited cell viability greater than 70% (p>0.05). ALP activity and protein synthesis showed no significant differences (p>0.05). TNF-α expression was significantly higher in the control group (41.25 ± 17.00 pg/mL) compared with PMMA (22.97 ± 7.08; p<0.01), PMMA+Z (25.76 ± 13.08; p<0.05), and PMMA+CAC (28.99 ± 14.71; p<0.05), suggesting inflammatory modulation. All groups presented mineralized nodules. In the wettability analysis, a numerical reduction in the contact angle was observed for PMMA+Z compared with pure PMMA, but without statistical significance (p>0.05). Conclusion: The addition of CAC and Z to PMMA resulted in more homogeneous surfaces, a trend toward increased wettability, and reduced TNF-α expression, without impairing cell viability or osteogenic potential, highlighting the promising potential of these formulations for bone regeneration. KEYWORDS Bone cement; Calcium aluminate; Osteogenesis; Polymethyl methacrylate; Zirconia.